2006
DOI: 10.1159/000090575
|View full text |Cite
|
Sign up to set email alerts
|

Periocular Microcystic Adnexal Carcinoma: Management and Outcome with Mohs’ Micrographic Surgery

Abstract: Purpose: To report a series of patients with periocular microcystic adnexal carcinoma (MAC) treated with Mohs’ micrographic surgery (MMS). Design: Prospective, interventional case series. Methods: This series included all patients treated with MMS for periocular MAC, who were monitored by the Skin and Cancer Foundation Australia between 1993 and 2002. Results: There were 5 patients (4 males, 1 female) with a mean age of 52 ± 12 years. Four tumors were located in the medial canthus and one in the lower lid.The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…188,189 Treatment consists of wide local excision and adjuvant radiation and chemotherapy. 190 Four of the tumors were initially misdiag-nosed as BCC or SCC, one of the cases had PNI, and all were successfully treated with MMS without recurrence at 5-year follow-up. 190 Four of the tumors were initially misdiag-nosed as BCC or SCC, one of the cases had PNI, and all were successfully treated with MMS without recurrence at 5-year follow-up.…”
Section: Cutaneous Melanomamentioning
confidence: 93%
See 1 more Smart Citation
“…188,189 Treatment consists of wide local excision and adjuvant radiation and chemotherapy. 190 Four of the tumors were initially misdiag-nosed as BCC or SCC, one of the cases had PNI, and all were successfully treated with MMS without recurrence at 5-year follow-up. 190 Four of the tumors were initially misdiag-nosed as BCC or SCC, one of the cases had PNI, and all were successfully treated with MMS without recurrence at 5-year follow-up.…”
Section: Cutaneous Melanomamentioning
confidence: 93%
“…188,189 Periocular microcystic adnexal carcinoma (MAC) was described in a case series of five patients: four with medial canthal lesions and one on the lower lid. 190 A review of 25 cases found MMS to be the most-effective treatment for MAC. 190 A review of 25 cases found MMS to be the most-effective treatment for MAC.…”
Section: Cutaneous Melanomamentioning
confidence: 99%
“…Patients treated with MMS did not require further treatments (4) (5) . MMS patients also had defects four times larger than clinically evident tumors (4) (6) (7,8) . Those treated with WLE had positive margins and required at least one additional surgical procedure as a result of a positive surgical margin (4,5) .…”
Section: Resultsmentioning
confidence: 97%
“…Thomas et al (6) found tumors were more likely to recur after MMS if their initial presentation was recurrent rather than primary. Recurrent tumors referred for MMS required a greater number of stages to clear and were more likely to have perineural invasion (PNI) (7,8) .…”
Section: Resultsmentioning
confidence: 99%
“…2 In 2006, Leibovitch and group showed a series of patients with squamous cell carcinoma who had 0% recurrence over 5 years. 5 Conventional techniques for treating squamous cell carcinoma result in 3 to 23% recurrence over 5 years.…”
Section: The Mohs Techniquementioning
confidence: 99%